Safety of Influenza Vaccination Among Hospitalized Patients. (4th October 2017) - Tartof, Sara; Liu, In-Lu Amy; Qian, Lei; Lewin, Bruno; Sy, Lina S; Tseng, Hung Fu; Hechter, Rulin; Jacobsen, Steven
Abstract: Background: Despite national recommendations, hospital influenza vaccination rates remain low. To address potential concerns regarding safety, we evaluated whether influenza vaccinatioqinPn during hospitalization increases utilization and/or evaluations for infection post-discharge. Methods: This retrospective cohort study was conducted among members of Kaiser Permanente Southern California aged ≥ 6 months who were hospitalized between September 1 st and March 31 st, from 2011 to 2014. With inverse probability of treatment weighting to adjust for confounding, we assessed the association between inpatient influenza vaccination and: rates of readmission, emergency department (ED) visits, outpatient visits, fever (temperature ≥38.0°C) and laboratory evaluations for infection (urine, blood, and wound culture; complete blood count) ≤ 7 days post-discharge. We modeled risk using 3 comparison groups: a) never vaccinated throughout the influenza season, b) vaccinated prior to hospitalization, and c) vaccinated >7 days post-discharge. Results: For the 3 models, 41, 733 hospitalizations with inpatient vaccination and a) 78, 809, b) 142, 479, and c) 21, 570 hospitalizations without inpatient vaccination were included. In adjusted analyses, compared with those never vaccinated, those vaccinated during hospitalization had marginally increased risk of ED visits (RR=1.08, 95% CI: 1.02–1.14) and post-discharge infection work-ups (1.06: 1.03–1.10). Compared with those with either prior vaccination or those with vaccination >7 days post-discharge, patients vaccinated during hospitalization had decreased risk of re-admission (0.84: 0.76–0.93; 0.80: 0.73–0.87, respectively), post-discharge fever (0.76: 0.63–0.92; 0.56: 0.47–0.67), and post-discharge infection work-ups (0.92: 0.89–0.96; 0.90: 0.86–0.93). Risk of outpatient visits ≤7 days post-discharge varied for the prior, never, and later vaccination comparison groups (0.93: 0.90–0.95; 1.09: 1.06–1.11; 1.11: 1.08.-1.14, respectively). Conclusion: There was no substantial increased risk of study outcomes associated with influenza vaccination during hospitalization. Our data support the recommendation of vaccinating hospitalized patients against influenza. Disclosures: H. F. Tseng, Novavax: Grant Investigator, Research grant